Comparison of Elongation and Calcification Patterns of Styloid Process on Panoramic and Cone Beam Computed Tomography Images - Hatice Yağmur Zengin; Serdar Uysal; Dilara Kara; Gökçen Akçiçek (Ankara University, 2023)
Purpose: The styloid process (SP) is part of the temporal bone that is a cylindric bony projection located immediately in front of the stylomastoid foramen. The normal reported length of the SP ranges from 20 to 32 mm and longer than 30 mm was considered to be elongated SP. The aim of this study was to compare the SP findings (length, type, and calcification pattern) on panoramic and cone beam computed tomography (CBCT) images. Materials and Methods: 163 patients who had panoramic and CBCT images in the same year were included to the study. On panoramic images calcifications beyond the mandibular foramen were classified as elongated SP while on CBCT images SP which had measured more than 30mm were accepted as elongated. Varying SP calcification classifications were reported by different researchers and in this study Langlais classification (Type 1 Elongated, Type 2 Pseudoarticulated, and Type 3 Segmented), the most accepted classification, was used. Calcification pattern were classified as calcified outlined, partially calcified, nodular, and completely calcified. Results: This study included 35 (21.5%) men, 128 (78.5%) women, 163 patients with mean age 46.13 ± 0.91 (21-65) years. On panoramic images 101 (62%) normal, 45 (27.6%) bilateral and 17 (10.4) unilateral elongated SP were detected. On CBCT images 85 (52.1%) normal, 56 (34.4%) bilateral and 22 (13.4%) unilateral elongated SP were detected. The agreement of the two imaging modalities was calculated as moderate (58.4%). Type 1 SP and partially calcified were the most common features of SP in both imaging modalities. Conclusion: Some SP cases, which are evaluated as not elongated in panoramic images, can be detected as elongated in CBCT images. Therefore, it is recommended to evaluate SP with CBCT in prevalence studies and cases where length is critical.